1994
DOI: 10.1073/pnas.91.20.9659
|View full text |Cite
|
Sign up to set email alerts
|

Dual regulation of Ca2+/calmodulin-dependent kinase II activity by membrane voltage and by calcium influx.

Abstract: The ubiquitous multifunctional protein kinase, Ca2+/calmodulin-dependent kinase II (CaMKII), is a cytosolic enzyme activated by the signal-transduction pathways that elevate intracellular free Ca2+. CaMKII is important in diverse cellular functions from modulating ionic channels in muscles (1-3) to encoding "memory" in neurons (4, 5). In heart muscle, ryanodine receptors (3) and phospholamban (6)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
145
0
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(154 citation statements)
references
References 24 publications
7
145
0
2
Order By: Relevance
“…Before ␣ 1 ARS, active CaMKII was detectable at the plasmalemma (Fig. 4 A and E) as reported (17). After ␣ 1 ARS (100 M phenylephrine) active CaMKII was still present at the plasmalemma (Fig.…”
Section: Effect Of 10 M Phenylephrine On Ical Measured By Using Thesupporting
confidence: 49%
See 1 more Smart Citation
“…Before ␣ 1 ARS, active CaMKII was detectable at the plasmalemma (Fig. 4 A and E) as reported (17). After ␣ 1 ARS (100 M phenylephrine) active CaMKII was still present at the plasmalemma (Fig.…”
Section: Effect Of 10 M Phenylephrine On Ical Measured By Using Thesupporting
confidence: 49%
“…It has been reported that CaMKII may directly phosphorylate the L-type Ca 2ϩ channel and regulate the positive feedback system that facilitates I Ca,L under physiological conditions (17,26). Our biochemical experiments showed that CaMKII is significantly activated by ␣ 1 ARS in adult rat isolated ventricular myocytes.…”
Section: Effect Of 10 M Phenylephrine On Ical Measured By Using Thementioning
confidence: 55%
“…It requires CaMKII-dependent phosphorylation, presumably of the α 1c -subunit or an associated protein [21,23,24]. Consequently, global CaMKII inhibition abolishes facilitation [22,24,34,51].…”
Section: Ca Facilitation Is Inhibited By Sr-targeted Camkii Inhibitionmentioning
confidence: 99%
“…CaMKII also mediates I Ca facilitation, where repeated depolarizations cause a Ca 2+ -and CaMKII-dependent increase in I Ca amplitude and slowing of inactivation [21][22][23][24]. As the Ltype Ca 2+ channel is in the sarcolemma, one might expect that SR localized AIP would not interfere with CaMKII mediated I Ca regulation.…”
Section: Introductionmentioning
confidence: 99%
“…In the cardiovascular system, PKA and PKC are both known to affect heart rate, 26,27 and PKA, 28,29 PKC, 30 -33 protein kinase G, 28,34 and CaM kinase 10,13,14,[35][36][37] all participate in the regulation of smooth and cardiac muscle [Ca 2ϩ ] i . Thus, the acute hemodynamic response to the systemic application of these inhibitory agents could be an important limitation in the development of novel approaches to antiarrhythmic therapy with the use of serine/threonine kinase inhibitory agents.…”
Section: Serine/threonine Kinases In Cardiovascular Systemmentioning
confidence: 99%